การคัดเลือกและปรับปรุงพันธุ์พิทูเนียดอกใหญ่โดยวิธีการผสมข้ามและทดสอบลูกผสมโดยการปักชำ - แย้มสุดใจ, จักรกฤษ; เตชะศีลพิทักษ์, ธัญญะ; สุขประเสริฐ, พัฒนา; พัฒนเกียรติ, สุวิสา; พิริยะภัทรกิจ, อนันต์ (Thai Journal of Science and Technology, 2018)
บทคัดย่อ พิทูเนียเป็นไม้ดอกที่มีสวยงามและได้รับความนิยมมากขึ้น โดยเฉพาะในกลุ่มของพิทูเนียที่ขยายพันธุ์โดยการปักชำได้ เนื่องจากมีความแข็งแรงและทนต่อสภาพแวดล้อมต่าง ๆ ได้ดี การศึกษาครั้งนี้ได้ปรับปรุงพันธุ์และคัดเลือกพันธุ์พิทูเนียดอกใหญ่ โดยศึกษาลักษณะบางประการของพิทูเนียในรุ่นลูกผสมจากพิทูเนียทางการค้า 8 พันธุ์ ผสมข้ามกับพันธุ์พิทูเนียเลื้อยที่สามารถขยายพันธุ์โดยการปักชำได้ พบว่าพิทูเนียแต่ละคู่ผสมในรุ่นลูกผสมมีเปอร์เซ็นต์การงอกของเมล็ดและการรอดชีวิตของต้นกล้าส่วนใหญ่สูงกว่าพิทูเนียในพันธุ์แม่ มีขนาดเส้นผ่านศูนย์กลางดอกเฉลี่ยตั้งแต่ 2.23-6.93 เซนติเมตร สีของดอกในรุ่นลูกผสมมีการกระจายตัวทั้งหมด 38 สี แต่ละคู่ผสมมีการกระจายตัวของสีดอก 5-13 สี ซึ่งสีทั้งหมดอยู่ในกลุ่มสีหลัก 4 กลุ่มสี ได้แก่ red-purple group, purple group, purple-violet group และ white group ลูกผสมพิทูเนีย 12 ต้น ได้คัดเลือกจากต้นที่มีลักษณะดอกใหญ่ มีสีสันสวยงาม และเกิดการผสมตัวเองไม่ติด เมื่อทดสอบการปักชำพบว่ามีลูกผสม 6 ต้น ที่ผ่านการคัดเลือก ได้แก่ ลูกผสม Grand White 1, Lime Green 1, Prism Blue 1, Prism Strawberry Sundae 1, Prism Strawberry Sundae 2 และ Prism Strawberry Sundae 3 โดยมีประสิทธิภาพการปักชำที่สูงไม่แตกต่างทางสถิติกับต้นพ่อ ซึ่งลูกผสมพิทูเนียที่ได้มีความเหมาะสมในการพัฒนาเป็นพันธุ์ทางการค้าต่อไปในอนาคต และสามารถใช้เป็นข้อมูลพื้นฐานในการปรับปรุงพันธุ์พิทูเนียต่อไปได้ คำสำคัญ : การทนต่อสภาพแวดล้อม; การปักชำ; การผสมตัวเองไม่ติด; การงอกของเมล็ด Abstract Petunia was a beautiful flowering plant that was very popular. Especially in petunia that was propagated by cutting technique because it was very strong and tolerate to the environment. So the aims of this study were to hybrid and to select petunia line for the grandiflora flower, by studying some characteristics of cross-breeding petunia from 8 commercial petunias with the trailing type. For this study found that the hybrid generation had a higher percentage of seed germination and the survival of seedling period than the commercial petunia. The average diameter of the flower was between 2.23 to 6.93 centimeter. Color distributions of the flower were up to 38 colors and in each cross-breeding had 5 to 13 colors. All of the colors based on 4 groups of colors which were Red-Purple Group, Purple Group, Purple-Violet Group and White Group. Twelve of hybrid petunias were selected by selection from large, beautiful colors flower and self-incompatibility. The 12 of the selected hybrid petunias were tested vegetative propagation by cutting technique. In this experiment found that 6 of them; i.e. Grand White 1, Lime Green 1, Prism Blue 1, Prism Strawberry Sundae 1, Prism Strawberry Sundae 2 and Prism Strawberry Sundae 3, have a higher rate of vegetative propagation by cutting technique, no significant difference to their male parent. For this study showed that these petunias were able to breed and develop for the commercial. Keywords: environmental tolerance; cutting; self-incompatibility; germination